Trajectories of change in general psychopathology levels among depressed adolescents in short-term psychotherapies. (2nd January 2023) - Fiorini, Guilherme; Saunders, Rob; Fonagy, Peter; ,; Midgley, Nick
Abstract: Objective: to identify and describe trajectories of change in general psychopathology ( p ) levels among depressed adolescents who received one of three types of short-term therapies (namely Cognitive–Behavioural Therapy, Short-Term Psychoanalytic Psychotherapy, and a Brief Psychosocial Intervention). Method: Participants were 465 adolescents with MDD who participated in an RCT comparing three treatments for depression. Narrow-band measures of depression, anxiety, obsessions-compulsions, and conduct problems were assessed at six-time points, and bifactor analysis was performed to extract p factor scores. These scores were submitted to Latent Class Growth Analyses to identify patterns of change over time. Results: Three different trajectories of change in p were identified. Two trajectories displayed reductions in p across time-points: one a rapid decrease, and the other slower but steady improvement. The third trajectory indicated a limited decrease in p up until the 12th week after baseline but no further improvement at subsequent time-points. Patients' baseline p significantly predicted their outcome trajectories. Conclusion: Exploring change in p seemed to describe more parsimoniously the patients' outcomes than the narrow-band assessment of depressive symptoms. Patients with high baseline p were more likely to have poorer outcomes, potentially indicating a need to develop more intensive and tailored treatments for this population.